Fundamentals of agricultural engineering - Kumar, Sanjay; Kumar, Vishal; Sahu, Ram Kumar (Ludhiana: Kalyani Pubishers, 2012)
This book contains five parts namely, Farm power, Farm mechinery, Renewable energy, Protected cultivation and post harvest technology, and soil, water and conservation engineering.
Agricultural Engineering Farm Power Farm Mechinery
Keywords: Agricultural engineering; Farm Power; Farm mechinery; Renewable energy; Food processing; Soil, Water and conservation engineering